INTERNAL AND EXTERNAL FACTORS AFFECTING FARMERS’ GROUP CAPABILITY IN ADAPTATION ON CLIMATE CHANGE - Wahyuning K Sejati; Sri Wahyuni; Tri Pranadji (UPT Penerbitan Universitas Jember, 2012)
Main problems faced by farmers group is their low capability, include in anticipating impact on climate change. This paper analyzed internal and external factors that affect farmer groups’ capability in adaptation on climate change. The data were collected from Indramayu District, West Java Province, that had ever experience in both flood and drought climate change impact. Data were collected through structured questionnaire and analyzed quantitatively. Both internal and external factors consisted of several aspects (elements), with the scale of answers ranged from 1 (one) indicating not adequate, to 4 (four) indicating very adequate. Results showed that the level of competence of farmers’ group members on climate change adaptation were less adequate. Efforts to handle the climate change in farmers’ group level hindered by insufficient knowledge, financial, and infrastructures. The capabilities of farmer groups in dealing with climate change impacts are relatively weak.